Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1186/1471-2407-12-289
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis viruses infection and risk of intrahepatic cholangiocarcinoma: evidence from a meta-analysis

Abstract: BackgroundStudies investigating the association between Hepatitis B virus (HBV) and hepatitis C virus (HCV) infections and intrahepatic cholangiocarcinoma (ICC) have reported inconsistent findings. We conducted a meta-analysis of epidemiological studies to explore this relationship.MethodsA comprehensive search was conducted to identify the eligible studies of hepatitis infections and ICC risk up to September 2011. Summary odds ratios (OR) with their 95% confidence intervals (95% CI) were calculated with rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 42 publications
2
76
1
2
Order By: Relevance
“…In studies from Western countries, hepatitis C virus (HCV) was shown to be a risk factor for CCA [54], whereas studies from Asia have shown more consistently HBV as a risk factor for IH-CCA [55]; a Japanese study confirmed findings from Western countries where IH-CCA association was stronger with HCV exposure than with HBV. The association of HBV and HCV with IH-CCA has also been recently confirmed in two meta-analyses of case-control and cohort studies with an odds ratio (OR) of 4.84 (2.41-9.71) for HCV and of 5.10 (2.91-8.95) for HBV [56,57]. The risk estimates for IH-CCA were increased for both HBV and HCV, whereas the association of HBV and IH-CCA was greater in Asian patients but lower for HCV and CCA as compared to Western patients [56,57].…”
Section: Hepatitis B and Cmentioning
confidence: 91%
“…In studies from Western countries, hepatitis C virus (HCV) was shown to be a risk factor for CCA [54], whereas studies from Asia have shown more consistently HBV as a risk factor for IH-CCA [55]; a Japanese study confirmed findings from Western countries where IH-CCA association was stronger with HCV exposure than with HBV. The association of HBV and HCV with IH-CCA has also been recently confirmed in two meta-analyses of case-control and cohort studies with an odds ratio (OR) of 4.84 (2.41-9.71) for HCV and of 5.10 (2.91-8.95) for HBV [56,57]. The risk estimates for IH-CCA were increased for both HBV and HCV, whereas the association of HBV and IH-CCA was greater in Asian patients but lower for HCV and CCA as compared to Western patients [56,57].…”
Section: Hepatitis B and Cmentioning
confidence: 91%
“…In addition, chronic infection with Salmonella typhi, Helicobacter species and the liver flukes Clonorchis sinensis and Opisthorchis viverrini has been implicated (1,(3)(4)(5). Palmer and Patel (6) and Zhou et al (7) previously reported that hepatitis B virus (HBV) and hepatitis C virus (HCV) infection is associated with an increased risk of intrahepatic cholangiocarcinoma (ICC). Recent studies from China, where the prevalence of the HBV carrier state is very high, have shown that HBV DNA and HCV RNA are detected in the tissue specimens of patients with ICC and extrahepatic cholangiocarcinoma (ECC) (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…A metaanalysis revealed that chronic hepatitis B and hepatitis C infection also increase the risk of this malignancy (Zhou et al, 2012). CCA is generally divided to intrahepatic and extrahepatic types.…”
Section: Introductionmentioning
confidence: 99%